Atomistic simulations of the mechanical properties of thin film materials - Say, Evan Jun Jie (Nanyang Technological University, 2022)
Molecular Dynamics (MD) simulation is a modern and effective tool to study the mechanical properties of micro- and nano- scale materials such as thin films, which may exhibit different behavior compared to bulk material. As such, MD simulation was used to atomistically study the mechanical properties of copper thin films under uniaxial tension, increasing the film’s length along the direction of strain, strain rate and externally applied heat in order to find the thickness where a bulk material begins exhibiting thin film properties or vice versa. It was found that applying a sudden and very high strain rate has the biggest effect on yield strength and elastic modulus, causing the copper thin film to exhibit a drastic increase in yield strength. As such, expected strain rate should be used as a primary design constraint over thickness in order to save material cost.